Parameterized Algorithms for Queue Layouts - Bhore, Sujoy; Ganian, Robert; Montecchiani, Fabrizio; Nöllenburg, Martin (Journal of graph algorithms and applications, 2022)
An $h$-queue layout of a graph $G$ consists of a linear order of its vertices and a partition of its edges into $h$ sets, called queues, such that no two independent edges of the same queue nest. The minimum $h$ such that $G$ admits an $h$-queue layout is the queue number of $G$. We present two fixed-parameter tractable algorithms that exploit structural properties of graphs to compute optimal queue layouts. As our first result, we show that deciding whether a graph $G$ has queue number $1$ and computing a corresponding layout is fixed-parameter tractable when parameterized by the treedepth of $G$. Our second result then uses a more restrictive parameter, the vertex cover number, to solve the problem for arbitrary $h$.